TRICHOGRAMMA AND METHODS OF ITS REPRODUCTION IN LABORATORIES. (Multidisciplinary Journal of Science and Technology, 2026)
In the modern integrated protection of plants from pests, the biological method is considered the most advanced, environmentally friendly, and safe approach for human health, nature, and warm-blooded animals. This method is harmless to bees and beneficial insects, and it is 8–10 times more cost-effective and efficient compared to chemical methods. Currently, 90% of pest control in our country is managed through biological methods. Taking this into account, the primary strategic plan involves a gradual transition to protecting 95% of crops using biological control methods.